Implementation of Competency-Based Human Resources Management on the Productivity of State Civil Apparatus in Medan City - Muhammad Alfahmi; Muhammad Albahi; Muhammad Alfikri (Mahesa Research Center, 2026)
This study aims to analyze the effect of competency-based human resource (HR) management implementation on the productivity of the State Civil Apparatus (ASN) in Medan City. The study employed a quantitative approach with an explanatory research design to examine the relationship between competency-based HR management and ASN productivity. The research was conducted within Regional Apparatus Organizations (OPD) of the Medan City Government. Data were collected through questionnaires distributed to ASN respondents using a five-point Likert scale and supported by documentation studies related to personnel management policies. The sampling technique used proportional random sampling, while data analysis was conducted using descriptive statistics and simple linear regression analysis. The findings indicate that the implementation of competency-based HR management in Medan City is categorized as good, particularly in aspects of HR planning, recruitment and selection, competency development, performance appraisal, and career development. In addition, ASN productivity was found to be relatively high in terms of work effectiveness, efficiency, quality of work results, and punctuality. The regression analysis revealed that competency-based HR management has a positive and significant effect on ASN productivity, with a determination coefficient showing that competency-based HR management contributes substantially to improving employee productivity. These findings confirm that the implementation of a competency-based HR management system can strengthen the professionalism, performance, and effectiveness of public sector employees. Therefore, local governments are encouraged to consistently enhance competency mapping, career development, and performance evaluation systems to support sustainable improvements in public service quality.